2003
DOI: 10.1076/neur.9.4.340.15553
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Sensitivity of a Sustained Attention Task to Frontal Damage: Convergent Clinical and Functional Imaging Evidence

Abstract: Despite frequent reports of poor concentration following traumatic brain injury, studies have generally failed to find disproportionate time-on-task decrements using vigilance measures in this patient group. Using a rather different definition, neuropsychological and functional imaging research has however linked sustained attention performance to right prefrontal function--a region likely to be compromised by such injuries. These studies have emphasised more transitory lapses of attention during dull and oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
110
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 144 publications
(122 citation statements)
references
References 41 publications
6
110
0
1
Order By: Relevance
“…Furthermore, the NA-sensitive SART test, sensitive to variations in NA availability (Bellgrove, et al, 2006,Greene, et al, 2009) and associated with right dFPLC-parietal activation (Manly, et al, 2003,O'Connor, et al, 2011 has also been shown to be selectively impaired by lesions to the right inferior frontal gyrus (Molenberghs, et al, 2009), which further cements the associations observed. Finally when NA is pharmacologically up-regulated, the dominant alterations in neural activation include the right dorsolateral prefrontal cortex (Chamberlain, et al, 2007,Grefkes, et al, 2010.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 83%
See 1 more Smart Citation
“…Furthermore, the NA-sensitive SART test, sensitive to variations in NA availability (Bellgrove, et al, 2006,Greene, et al, 2009) and associated with right dFPLC-parietal activation (Manly, et al, 2003,O'Connor, et al, 2011 has also been shown to be selectively impaired by lesions to the right inferior frontal gyrus (Molenberghs, et al, 2009), which further cements the associations observed. Finally when NA is pharmacologically up-regulated, the dominant alterations in neural activation include the right dorsolateral prefrontal cortex (Chamberlain, et al, 2007,Grefkes, et al, 2010.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 83%
“…As described above, there are at least three different supramodal attentional systems for selection, control and vigilance respectively, but it is only the latter which has a strong linkage to NA activity and a clear right hemisphere fronto-parietal neural basis as shown in many studies (Manly, et al, 2003,Paus, et al, 1997,Sturm, et al, 1999. This network monitors and modulates activity in subcortical regions governing arousal to match current task demands (Critchley, et al, 2002,Foucher, et al, 2004.…”
mentioning
confidence: 99%
“…However, studies using traditional vigilance tests have often failed to fi nd disproportionate defi cits (see Manly et al, 2003 ). Robertson, Manly, Andrade, Baddeley, and Yiend ( 1997 ) developed a new computerized measure designed to be more sensitive to transient lapses in attention than traditional vigilance and continuous performance tests; the Sustained Attention to Response Test (SART).…”
Section: Sustained Attention After Traumatic Brain Injurymentioning
confidence: 99%
“…These included: National Adult Reading Test (NART) (Nelson, 1982;Nelson & Willison, 1991), Hospital Anxiety and Depression Scale (HADS) (Zigmond & Snaith, 1983), Frenchay Aphasia Screening Test (FAST) (Enderby et al, 1987), and Frontal Assessment Battery (FAB) (Dubois et al, 2000). (Robertson et al, 1996) and the Sustained Attention to Response Task (Robertson et al, 1997, Manly et al, 2003, Dockree et al, 2006. Participants undertook three tasks of sustained attention: the Fixed SART, Random SART and the DART.…”
Section: Screening Testsmentioning
confidence: 99%